Application of a bacterial whole cell biosensor for the rapid detection of cytotoxicity in heavy metal contaminated seawater. (June 2018) - Cui, Zhisong; Luan, Xiao; Jiang, Huichao; Li, Qian; Xu, Guangfei; Sun, Chengjun; Zheng, Li; Song, Yizhi; Davison, Paul A.; Huang, Wei E.
Abstract: A toxicity biosensor Acinetobacter baylyi Tox2 was constructed with the host strain A. baylyi ADP1 harboring a new and medium-copy-number plasmid pWH1274_lux, and was applied to detect the cytotoxicity of heavy metal contaminated seawater. The gene cassette luxCDABE was controlled by constitutively expressed promoter Ptet on pWH1274_lux and the bioluminescence intensity of the biosensor reduces in proportional to the concentrations of toxic compounds. A. baylyi Tox2 exhibits tolerance to salinity, hence it is applicable to seawater samples. A. baylyi Tox2 and Mugilogobius chulae were exposed to different concentrations of heavy metals (Hg 2+, Zn 2+, Cu 2+, and Cd 2+ ) in artificial seawater for performance comparison and Pearson correlation analysis showed a significant correlation (p < 0.01) between A. baylyi Tox2 toxicity detection and the fish ( M. chulae ) exposure test. This suggests that the performance of A. baylyi Tox2 is comparable to the conventional fish toxicity test in terms of cytotoxicity detection of heavy metal contaminated seawater. Furthermore, A. baylyi Tox2 was used to evaluate cytotoxicity of field-collected seawater samples. The results indicate that there was a significant correlation between the luminescence inhibition ratio (IR) of A. baylyi Tox2 and heavy metal concentrations detected by ICP-MS in the samples. Two seawater samples, which contained a high concentration of total heavy metals, exhibited stronger cytotoxicity than the samples containing low concentrations of heavy metals. In conclusion, A. baylyi Tox2 can be used as an alternative tool to aquatic animals for the evaluation of the cytotoxicity of heavy metal contamination in the marine environment. Graphical abstract: Highlights: A biosensor Acinetobacter baylyi Tox2 was developed for rapid toxicity detection. The biosensor performs well in artificial seawater amended by heavy metals. The toxicity by LBTA is in good agreement with that of the animal toxicity test. We applied A. baylyi Tox2 to detect the toxicity of in situ contaminated seawaters. The toxicity by LBTA is in good agreement with the chemical analysis.